ICT and environmental sustainability: A global perspective - Añón Higón, Dolores; Gholami, Roya; Shirazi, Farid (Telematics and informatics, 2017)
•ICT may have positive and negative environmental impacts, leading to a U-shaped relationship.•We explore this non-linear relationship for a sample of developed and developing economies from 1995 to 2010.•The results confirm that the relationship between ICT and CO2 emissions is an inverted U-shaped relationship. The positive and negative environmental impacts of information and communication technologies (ICTs) are widely debated. In theory, ICT is among the sources contributing to the increasing levels of CO2 emissions in terms of production of ICT machinery and devices, energy consumption, and recycling of electronic waste. However, ICT is also expected to reduce CO2 emissions on a global scale by developing smarter cities, transportation systems, electrical grids, industrial processes, and energy saving gains. These two effects work in opposite direction, creating an inverted-U relationship between ICT and CO2 emissions. The aim of this study is to investigate this non-linear relationship between ICT and CO2 emissions on a global scale. Given that global warming is a global issue, it is necessary to look at this relationship in countries at all levels of development. To this end, we use a panel data set consisting of 142 economies, split into 116 developing and 26 developed countries, over the period 1995–2010. The results of our empirical study confirm that the relationship between ICT and CO2 emissions is an inverted U-shaped relationship. Moreover, while for the sample of developing countries, the ICT turning point is well above the mean value, the opposite is true for the sample of developed countries. This implies that many developed countries have already attained the level of ICT development, at which CO2 emissions decreases as the level of ICT development improves further.